2020
DOI: 10.1088/1361-665x/abb0a1
|View full text |Cite
|
Sign up to set email alerts
|

A new invertible model of magnetorheological damper based on sigmoid function

Abstract: As an intelligent device, the magnetorheological (MR) damper has received extensive attention in many fields. However, in the real-time control system, it is still extremely necessary to develop a simple, accurate and invertible dynamic model of the MR damper. In this work, a new invertible MR dynamic model based on sigmoid function is proposed. According to the experimental data of a common MR damper, it is assumed that the damping force at zero velocity under constant current is only related to current and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The sigmoid model (Lu et al, 2020) is used to describe the dynamic behavior of the MR damper, as shown in Equations (2a) (2b).…”
Section: Inverse Model Of Mr Dampermentioning
confidence: 99%
See 2 more Smart Citations
“…The sigmoid model (Lu et al, 2020) is used to describe the dynamic behavior of the MR damper, as shown in Equations (2a) (2b).…”
Section: Inverse Model Of Mr Dampermentioning
confidence: 99%
“…However, common reversible models usually cannot accurately describe the dynamic behavior of MR damper at different frequencies, such as polynomial models (Dong et al, 2009, 2010; Xiao Min et al, 2009) and hyperbolic tangent models (Hu et al, 2017; Kecik et al, 2014), or the recognition processes of the models are complicated (Yu et al, 2017), such as Adaptive Neuro-Fuzzy Inference Inverse Model (ANFIS) (Nguyen et al, 2017; Zong et al, 2012, 2013). Recently, Zhang et al proposed a reversible sigmoid model (Lu et al, 2020), which has good fitting accuracy for damping forces at different frequencies and different currents, but the actual control effect of this model has not yet been experimentally verified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the Bouc-Wen models are accurate in predicting the dynamic response of MR damper but they are usually highly computationally demanding due to the involvement of many parameters and differential equations (Spencer et al, 1997; Yang et al, 2004). Moreover, the existence of differential equations makes it harder to obtain the inverse models of Bouc-Wen models which are necessary for the current identification of MR dampers in real-time control systems (Cheng et al, 2020; Lu et al, 2020). The Bingham plastic model, which is originally proposed for characterizing the materials that behave as a rigid body at low shear rates and as a viscous fluid at high shear rates, is not only computationally efficient than the Bouc-Wen models but also easy to be inverted to achieve effective and efficient real-time control.…”
Section: Dynamic Modeling Of Mr Dampermentioning
confidence: 99%
“…As for static models, several researchers have suggested either nonlinear functions or soft-computing techniques. For instance, researchers have utilized the static sigmoid function [ 20 , 24 ], Gompertz function [ 25 ], hyperbolic tangent function [ 26 ], and neural networks [ 27 , 28 , 29 ]. These investigations came with a drawback—they require a large database to tune in the corresponding functions.…”
Section: Introductionmentioning
confidence: 99%